Answer:
Step-by-step explanation:
The average rate of change is the change in the number of visitors divided by the change in the number of months.
1. Change in number of visitors
Change in visitors = 182 -125 = 57 visitors
2. Change in number of weeks
Change in time = 5 - 2 = 3 months
3. Average rate of change
![\begin{array}{rcl}\text{Average rate of change} &= &\dfrac{\text{change in visitors}}{\text{change in months}}\\\\&= &\dfrac{\text{57 visitors}}{\text{3 mo}}\\\\& = & \textbf{19 visitors/mo}\\\end{array}\\\text{The average rate of change is $\large \boxed{\textbf{19 visitors/mo}}$}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Brcl%7D%5Ctext%7BAverage%20rate%20of%20change%7D%20%26%3D%20%26%5Cdfrac%7B%5Ctext%7Bchange%20in%20visitors%7D%7D%7B%5Ctext%7Bchange%20in%20months%7D%7D%5C%5C%5C%5C%26%3D%20%26%5Cdfrac%7B%5Ctext%7B57%20visitors%7D%7D%7B%5Ctext%7B3%20mo%7D%7D%5C%5C%5C%5C%26%20%3D%20%26%20%5Ctextbf%7B19%20visitors%2Fmo%7D%5C%5C%5Cend%7Barray%7D%5C%5C%5Ctext%7BThe%20average%20rate%20of%20change%20is%20%24%5Clarge%20%5Cboxed%7B%5Ctextbf%7B19%20visitors%2Fmo%7D%7D%24%7D)
Answer:
b is the answer by solomon
Answer:
![y=-2x+3](https://tex.z-dn.net/?f=y%3D-2x%2B3)
Step-by-step explanation:
Given: ![8x+4y=12](https://tex.z-dn.net/?f=8x%2B4y%3D12)
To solve for y, let us first isolate y on one side of the equation. We can do this by subtracting
from the left and move it to the right. We then get:
![4y=12-8x](https://tex.z-dn.net/?f=4y%3D12-8x)
Now, we have y isolated. We now have to remove the 4 from the y. The only way to do this is divide both sides by 4. We then get our final answer:
![y=3-2x](https://tex.z-dn.net/?f=y%3D3-2x)
We can clean this up by putting it in a common form, slope-intercept form:
![y=-2x+3](https://tex.z-dn.net/?f=y%3D-2x%2B3)
Answer:
Make an eqaution from here.
Let’s make evening 2 “x”
So the first evening has 9 less then the secon evening so…
x-9
Of course theres the second evening (x).
X-9+x
Then the third evening has 4 times as much as the second meeting so…
x-9+x+4x
And when solved, it has to equal 105.
So solve from here.
Combine like terms.
6x-9=105
Isolate
6x=114
x= 19
First evening is 9 less then 19, so 10.
The second evening was 19 calls.
The third evening was 4 times the second evening so, 19*4= 76
1st night = 10
2nd night= 19 calls
Thrid night= 76 calls
Step-by-step explanation:
c) since m = undefined => the equation is
x = -2
d) the equation is
y-2= -1/7 (x+7)
=> y = -1/7 x -1+2
<=> y = -1/7 x + 1